IMPROVEMENT OF ECONOMIC, ORGANIZATIONAL AND LEGAL MECHANISMS OF MARKET DEVELOPMENT IN UZBEKISTAN - Kholmirzaev Toir Ruzimurodovich; Toshpulatov Jahongir Samar ugli (Web of Journals Publishing, 2024)
The article examines the state of the insurance market and the existing problems in our country, as well as the need to liberalize insurance relations in the development of this market.
Keywords: insurance activity, insurance market, authorized capital, minimum requirements, insurance control, insurance market development agency.